Novel Stimuli-Responsive Pectin-PVP-Functionalized Clay Based Smart Hydrogels for Drug Delivery and Controlled Release Application - Rehmat, Shabnam; Rizvi, Nayab Batool; Khan, Saba Urooge; Ghaffar, Abdul; Islam, Atif; Khan, Rafi Ullah; Mehmood, Azra; Butt, Hira; Rizwan, Muhammad (Frontiers in Materials, 2022)
Stimuli-responsive drug delivery systems are urgently required for injectable site-specific delivery and release of drugs in a controlled manner. For this purpose, we developed novel pH-sensitive, biodegradable, and antimicrobial hydrogels from bio-macromolecule pectin, polyvinylpyrrolidone (PVP), 3-aminopropyl(diethoxy)methyl silane (3-APDEMS), and sepiolite clay via blending and solution casting technique. The purified sepiolite (40 um) was functionalized with 3-APDEMS crosslinker (ex-situ modification) followed by hydrogels fabrication. FTIR and SEM confirmed crosslinked structural integrity and rod-like morphology of hydrogels respectively. The swelling properties of hydrogels could be controlled by varying the concentration of modified clay in pectin/ PVP blends. Moreover, the decrease in pH increased the swelling of hydrogels indicating the pH-responsiveness of hydrogels. All hydrogels were degraded after 21 days in phosphate buffer saline pH 7.4(human blood pH). In-vitro cytotoxicity against 3T3 mouse fibroblast cell line analysis confirmed cytocompatibility of all hydrogels. Ceftriaxone sodium (CTX-S) was selected as a model drug. The release profile of the hydrogel showed 91.82% release in PBS for 2 h in a consistent and controlled manner. The chemical structure of the drug remained intact during and after release confirmed through UV-Visible spectroscopy. Overall, these hydrogels could be used as potential scaffolds for future biomedical applications.